2021
DOI: 10.1111/spc3.12639
|View full text |Cite
|
Sign up to set email alerts
|

Conspiracy beliefs and the individual, relational, and collective selves

Abstract: Recent empirical and theoretical developments suggest that endorsement of conspiracy theories can arise from the frustration of social motives. Taking this further, the current review integrates theorising on processes relating to three selves-the individual, relational, and collective self and outlines their associations with conspiracy beliefs. In doing so, we argue that motives pertaining to the individual self (e.g., narcissism, need for uniqueness) are linked to belief in conspiracy theories to deflect bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 134 publications
1
50
0
Order By: Relevance
“…In our final set of meta-analyses, we confirmed that conspiracy beliefs are associated with motivations to defend and enhance the image of oneself and the groups that one belongs to (but were less consistently related to more secure forms of self and group-worth; e.g., . We also provided tentative evidence for the notion that conspiracy beliefs may act as a compensation for experiences of social exclusion, suggesting that they could be appealing in their ability to provide individuals with opportunities to gain social support through the sharing of interests and concerns (see MOTIVES AND CONSPIRACY BELIEFS Biddlestone et al, 2021). Moderation analyses revealed that the strengths of effect sizes for the relational self increased as the mean age of the sample increased.…”
Section: Social Needsmentioning
confidence: 73%
See 1 more Smart Citation
“…In our final set of meta-analyses, we confirmed that conspiracy beliefs are associated with motivations to defend and enhance the image of oneself and the groups that one belongs to (but were less consistently related to more secure forms of self and group-worth; e.g., . We also provided tentative evidence for the notion that conspiracy beliefs may act as a compensation for experiences of social exclusion, suggesting that they could be appealing in their ability to provide individuals with opportunities to gain social support through the sharing of interests and concerns (see MOTIVES AND CONSPIRACY BELIEFS Biddlestone et al, 2021). Moderation analyses revealed that the strengths of effect sizes for the relational self increased as the mean age of the sample increased.…”
Section: Social Needsmentioning
confidence: 73%
“…The research we have reviewed so far suggests that conspiracy theorising is attractive to people whose basic psychological needs are unmet, and more specifically, that it is strongest when people's epistemic, existential, and social needs are thwarted (Douglas et al, 2017; see also Douglas et al, 2019;Biddlestone et al, 2021). Although this framework has proven popular in investigating the motivations associated with conspiracy beliefs, to date no systematic, formal analysis of these studies has been conducted.…”
Section: The Need To Synthesise Broad Theoretical Claimsmentioning
confidence: 99%
“…Importantly, studies on conspiracy thinking are mainly focused on identifying an array of personality characteristics that are linked to a conviction that others are secretly conspiring against us. In other words, instead of analyzing whether a particular conspiracy theory is true or false, social scientists usually try to understand the role of adopting such beliefs in dealing with distress (e.g., Marchlewska et al, 2021 ), self-evaluation problems ( Cichocka, Marchlewska, & Golec de Zavala, 2016 ) uncertainty ( Marchlewska et al, 2018 ), or other types of psychological weaknesses (for a review see Biddlestone et al, 2021 ). They also explore potential consequences of adopting conspiratorial explanations (e.g., the relationship between vaccination conspiracy beliefs and lower support for voluntary vaccination policy; Cislak et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research found conspiracy beliefs to predict prejudice, negative out-group attitudes, and violence [ 28 , 29 ]. This is because adopting conspiratorial explanations is closely related to lower levels of trust, scapegoating, and projecting societal problems onto real or imagined enemies who can be blamed for individual or collective problems [ 30 ]. One may ask, however, whether conspiracy beliefs always must necessarily bring damaging consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our research was to investigate the prevalence of food industry conspiracy beliefs as well as factors associated with these beliefs. Previous research found that conspiracy beliefs are usually activated when facing different types of psychological threat [ 51 ] and lead mainly to maladaptive individual and societal outcomes [ 30 , 52 ]. In this work we claim that concomitants of conspiracy beliefs may depend on the context so that in some cases belief in conspiracy theories may lead not only to negative consequences for the self [ 20 , 30 ], but paradoxically, be associated with adaptive, healthy, behaviors.…”
Section: Introductionmentioning
confidence: 99%